2019
DOI: 10.15252/embj.2018101109
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and proteomic profiling reveals centrosome‐independent features of centriolar satellites

Abstract: Centriolar satellites are small electron‐dense granules that cluster in the vicinity of centrosomes. Satellites have been implicated in multiple critical cellular functions including centriole duplication, centrosome maturation, and ciliogenesis, but their precise composition and assembly properties have remained poorly explored. Here, we perform in vivo proximity‐dependent biotin identification (Bio ID ) on 22 human satellite proteins, to identify 2,113 high‐confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
144
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(155 citation statements)
references
References 101 publications
10
144
1
Order By: Relevance
“…CCDC57 was one of the uncharacterized proteins that stood out in these maps due to its high proximity to centriole duplication proteins. Notably, CCDC57 was recently identified as a component of the centriolar satellite interactome, which corroborates the functional relationship between centriolar satellites and centriole duplication (Gheiratmand et al, 2019). Here, we characterized CCDC57 as a centriole duplication protein required for recruitment of the microcephaly-associated proteins CEP63, CEP152, and PLK4 to the centrosome.…”
Section: Introductionsupporting
confidence: 83%
“…CCDC57 was one of the uncharacterized proteins that stood out in these maps due to its high proximity to centriole duplication proteins. Notably, CCDC57 was recently identified as a component of the centriolar satellite interactome, which corroborates the functional relationship between centriolar satellites and centriole duplication (Gheiratmand et al, 2019). Here, we characterized CCDC57 as a centriole duplication protein required for recruitment of the microcephaly-associated proteins CEP63, CEP152, and PLK4 to the centrosome.…”
Section: Introductionsupporting
confidence: 83%
“…Notably, fibrogranular material in MCCs was shown to contain the protein PCM1 39 , which is also required to scaffold the assembly of the 'pericentriolar satellites' that are found in non-MCCs. It is therefore possible that the fibrogranular material is functionally equivalent to the pericentriolar satellites of non-MCCs [40][41][42][43] . Additional studies will be required to identify the minimal components involved in centriole assembly and number control, and to define the role of DEUP1 and the deuterosome in MCCs.…”
Section: Discussionmentioning
confidence: 99%
“…EMBL EBI Expression Atlas ebi.ac.uk/gxa). Moreover, two independent proximity labeling studies identified LUZP1 as a proximal interactor of centriole (35) and centriolar satellite-related proteins (45). Here, we report that LUZP1 forms a basket-like 3D structure surrounding the proximal end of both centrioles.…”
Section: Discussionmentioning
confidence: 99%